Sustainable biodiesel production: importance of feedstock resources and production methods - Mhetras, Nutan; Gokhale, Digambar (RSC Advances, 2025)
Biodiesel made from renewable feedstock can be considered as a renewable and sustainable alternative to fossil fuels. This review briefly covers the historical background on biodiesel and discusses the various renewable feedstock sources for biodiesel production. It also emphasizes the importance of not only the feedstock quality but also on biodiesel quality that satisfies the ASTM D6751 and EN 1421 standards. In addition, the review describes various methods for biodiesel production with major thrust on transesterification, which is the key process. It also highlights the use of different types of catalysts including acidic, basic, bi-functional, and enzymes in the transesterification reaction. The review concludes by emphasizing the importance of pursuing further research and development to address the challenges in developing low cost and eco-friendly processes for biodiesel production.